Structural performance assessment of high strength concrete containing spent garnet under three point bending test - Budiea, A. M. A.; Sek, W. Z.; Mokhatar, S. N.; Khairunisa, Muthusamy; Yusoff, A. R. M. (IOP Publishing, 2021)
The utilization of river sand for miscellaneous construction purposes had directly increased due to rapid growth of construction industry. This fact caused over exploitation of riverbeds and troubled the eco-system. This study aims to find out the optimum percentage of spent garnet in high strength concrete and to forecast the structural performance of high strength concrete containing spent garnet with the previous research results. This study focusing on comparing and forecasting the utilization of 0%, 10%, 20%, 30% and 40% spent garnet as a sand replacement in high strength concrete at the age of 28 days. The level of 20% replacement of sand seen to be the optimum percentage of spent garnet for this concrete mixture to enhance its structure performance. It is concluded that, utilization of spent garnet in high strength concrete production able to reduce the dependency on river sand and lesser the waste from landfill.